Neonatal hypoglycemia and associated factors at Wangaya General Hospital - Putri, Asterisa Retno; Arumndari, Runi; Liman, Claudia Natasha; Suarca, Kadek; Suryawan, I Wayan Bikin (Indonesian Journal of Multidisciplinary Science, 2023)
In the early hours to early days of life, managing low blood glucose levels and screening infants at risk are common problems in the care of newborns. Still missing, though, is a precise definition of newborn hypoglycemia. The purpose of this study is knowing that pregnancy hypertension/preeclampsia/eclampsia, prematurity, small-gestational-weight (SGA), large-gestational-weight (LGA), asphyxia, and sepsis are risk factors associated with neonatal hypoglycemia. The type of research conducted was a cross-sectional retrospective analytic study on infants in the perinatology room at Wangaya Hospital in 2022. The sample in this study consisted of 18 hypoglycemia babies and 18 normoglycemia babies taken by purposive sampling with matching hypertension/preeclampsia/eclampsia pregnancy, prematurity, SGA, LGA, asphyxia and sepsis. Data collection used medical record data and perinatology register data. Statistical tests used were Chi-Square and logistic regression with a 95% confidence interval. The results showed that prematurity was an associated risk factor (OR=2.78; 95% CI=1.437-5.379), asphyxia and sepsis also showed statistical significance (OR=2.07; 95% CI=1.221-3.513) (OR=2.27; 95% CI=1.257-4.109). In multivariate analysis, there was no statistical significance among other factors (p-value 0.019). Prematurity, asphyxia, and sepsis were risk factors associated with the incidence of neonatal hypoglycemia with odds of 2.78 times, 2.07 times and 2.27 times respectively compared to the control population. However, in the multivariate analysis, there was no relationship between one factor to another factor that influenced each other in being a risk factor associated with hypoglycemia at Wangaya Hospital.